Gharar in Islamic Economics: Challenges, Regulation, and Implementation in Business - Arpizal; Sabaruddin Chaniago (Journal of Global Islamic Economic Studies, 2025)
The principle of gharar is one of the important pillars in Islamic economics that functions to maintain justice, transparency, and certainty in every economic transaction. The prohibition against gharar is based on the hadith of the Prophet Muhammad which prohibits buying and selling that contains an element of uncertainty (bay' al-gharar). In the modern context, this principle faces serious challenges due to the development of the global economic system, the emergence of digital financial instruments, and complex technology-based business models. Therefore, this study aims to analyze the basic concepts and theoretical foundations of gharar, identify the challenges and regulations of its application in contemporary economic systems, and evaluate the implementation of anti-gharar principles in modern business practices. The method used is a qualitative approach with literature studies, with data searches through scientific sources on Google Scholar which include journals, books, and fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) related to gharar. The results of the study show that the gharar ban has strong relevance in maintaining economic stability and ethics in the midst of global business dynamics. Sharia regulations, such as the DSN-MUI fatwa, are an important instrument in ensuring compliance with this principle, especially in the Islamic banking, insurance, and fintech sectors . In conclusion, gharar is not just a normative prohibition, but a moral and legal guideline for building a fair, transparent, and sustainable business system in accordance with Islamic values.